Pemberdayaan Masyarakat Dalam Advokasi Stunting Melalui Forum Desa - Ryan Agus Faisal; Halimah Tusakdiyah; Ramada Sandi (STIKES Columbia Asia Medan, 2024)
Stunting is one of the chronic nutritional problems that remains a serious challenge in Indonesia, particularly in rural areas. This condition not only affects children's physical growth but also their cognitive development and long-term productivity. The low level of public awareness regarding balanced nutrition and proper parenting practices is a major factor contributing to the high prevalence of stunting. Therefore, community empowerment through village forums as a platform for advocacy, education, and cross-sector collaboration is essential. This activity aims to enhance the capacity of village communities to understand, prevent, and address stunting through participatory approaches. The methods applied include training for posyandu cadres, group discussions, and the establishment of village stunting forums involving community leaders, health workers, and local government officials. The results indicate a significant improvement in public knowledge and awareness regarding stunting prevention. The village forum also serves as a coordination center for policy advocacy and the implementation of nutrition programs at the local level. Thus, community empowerment through village forums has proven to be an effective strategy to strengthen community participation and enhance synergy between government, health institutions, and local residents in reducing stunting prevalence at the village level.